(untitled) (Bangladesh Medical Journal, 2010)
The first five years of a child’s life i.e early childhood period ,often called the ’formative years’, are absolutely critical for the development, performance and success of the child throughout his life. It is the period in which the foundations for future life take place. The appropriateness and quality of care and childhood opportunities and experiences that a child receives during this period may ultimately determine adult hood and his/her ability to contribute to society. Recent neuroscience shows that development of the brain over the first five years is more rapid and intensive and more vulnerable to external influence or the environment. Opportunities taken or missed during this period will have profound influence in the future life of a child. DOI: 10.3329/bmj.v39i1.6230 Bangladesh Medical Journal 2010; 39(1): 28-30